An Atlas of the Himalayas by a 19th Century Tibetan Lama : a Journey of Discovery - Lange, Diana (Brill's Tibetan studies library, 2020)
Diana Lange's patient investigations have, in this wonderful piece of detective work, solved the mysteries of six extraordinary maps of routes across Tibet, clearly hand-drawn in the late 1850s by a local artist, known as the British Library's Wise Collection. Diana Lange now reveals not only the previously unknown identity of the Scottish colonial official who commissioned the maps from a Tibetan Buddhist lama, but also the story of how the Wise Collection came to be in the British Library. The result is both a spectacular illustrated ethnographic atlas and a unique compendium of knowledge concerning the mid-19th century Tibetan world, as well as a remarkable account of an academic journey of discovery. It will entertain and inform anyone with an interest in this fascinating region. This large format book is lavishly illustrated in colour and includes four separate large foldout maps.